Effects of different dietary energy contents on milk urea concentration in stall-fed dairy sheep - Giovanetti V.; Decandia M.; Boe F.; Zerbini E.; Cannas A.; Molle G. (Nutritional and foraging ecology of sheep and goats, 2009)
The objective of this study was to evaluate the effects of dietary energy content on milk urea concentration in mid and late lactating Sarda ewes, kept in metabolic crates. Forty ewes were blocked in 8 homogeneous groups, of 5 animals each, and fed with 8 pelleted diets spanning from low (i.e. fibrous diets: 1.2-1.4 Mcal of NEL) to high (high-starch diets: 1.7-1.9 Mcal of NEL) energy contents and with fairly similar crude protein (CP) concentration (18.4% DM on average). Based on their main ingredient, diets were denominated: corn meal (CM), wheat middlings (WM), corn flakes (CF), barley meal (BM), corn cobs (CC), beet pulp (BP), alfalfa (AA) and soybean hulls (SH). In both mid- and late-lactating sheep, milk urea concentration was affected by diet with the highest values in AA fed ewes. A negative linear relationship was found between dietary energy (NEL, Mcal/kg DM) and milk urea (MUC, mg/100 ml) concentrations (MUC = 127.86 - 51.46 × NEL; R2 = 0.88, RMSE = 3.95, P < 0.001). The soluble protein fractions B1 and, to a lesser extent, A were able to contribute in explaining MUC variations. The ratio CP/NEL (g/Mcal) was also strictly related to MUC (MUC = -14.68 + 0.51 × × CP/NEL; R2 = 0.86, RMSE = 4.29, P < 0.001). This research suggests that dietary energy content can play a key role in modulating the relationship between CP or its fractions and milk urea in dairy sheep.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)